The Influence of Brand Image and Product Quality Perception on Consumer Purchase Intention for Axioo Laptops : A Study Among Students at Universitas Sembilanbelas November Kolaka - Risdayanti Risdayanti; Andry Stepahnie Titing; Ismanto Ismanto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study examines the influence of brand image and perceived product quality on consumer purchase intention for Axioo laptops, focusing on students at Universitas Sembilanbelas November Kolaka. As a local laptop brand in Indonesia, Axioo faces intense competition and low brand awareness among younger consumers. The study uses a quantitative explanatory approach with a sample of 376 students selected via purposive sampling. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling with the SmartPLS 4.0 application. The results indicate that both brand image and perceived product quality have a significant and positive effect on purchase intention. The R-square value shows that 64.7% of the variance in purchase intention is explained by the two independent variables. These findings suggest that strengthening brand image and improving product quality are critical strategies to increase consumer acceptance and market competitiveness for local technology products like Axioo laptops.